2022
DOI: 10.15586/aei.v50i5.582
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of educational intervention on Autoinjector Technique for caregivers and paediatric patients with food allergies: A literature review

Abstract: Background and objective: The incidence of food allergy among children is on the rise. Children who are diagnosed with a food allergy receive long-term treatment for allergy management from allergy specialists, nurses and dieticians. This management may include the prescription of an adrenaline autoinjector (AAI) if the child is at risk of a severe allergic reaction (anaphylaxis). Therefore, it is important that parents of children with allergies are trained in the recognition of anaphylaxis and in the correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
(62 reference statements)
2
7
0
Order By: Relevance
“…However, in a systematic review, a correct AAI administration technique was shown to be low, with only 32% of parents/caregivers successfully demonstrating correct AAI technique [7]. Similar findings were found in a recent review of the literature, regarding the effectiveness of educational intervention on AAI administration ability, where it was found that the AAI administration success among parents ranged significantly, and the success rates varied from 5.6 to 84% [8]. This may reflect several issues, including training effectiveness or lack of training, user stress during administration, or inherent differences consequent of the design of the individual auto-injector [3].…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, in a systematic review, a correct AAI administration technique was shown to be low, with only 32% of parents/caregivers successfully demonstrating correct AAI technique [7]. Similar findings were found in a recent review of the literature, regarding the effectiveness of educational intervention on AAI administration ability, where it was found that the AAI administration success among parents ranged significantly, and the success rates varied from 5.6 to 84% [8]. This may reflect several issues, including training effectiveness or lack of training, user stress during administration, or inherent differences consequent of the design of the individual auto-injector [3].…”
Section: Introductionsupporting
confidence: 74%
“…The high occurrence of switching brands of AAI among caregivers, as well as the suboptimal training in the different brands of AAI, are concerning findings. Research comparing the administration of different AAI devices and the effects of brand switching is sparse, with a recent review finding only three previous such studies [8]. One study found that success rates dropped after switching between a one-cap (Epipen ® or Jext ® ) and a twocap (Anapen ® ) device without training, (16/45, 36%), compared with participants switched between different single-cap devices (49/63, 78%; p < 0.0001) [14].…”
Section: Discussionmentioning
confidence: 99%
“…with AAI use. 15,16 While the numbers in each subgroup analysis were small, this study suggests that caregivers with higher annual household incomes were more likely to believe they were responsible for training their child to recognize anaphylaxis and AAI use and exhibited higher confidence in doing so. This may reflect increased access to specialist health care in this group and therefore additional training in AAI use.…”
Section: Readiness Factorsmentioning
confidence: 82%
“…Evidently, the delivery of caregiver training requires improvement. One review of caregiver training in anaphylaxis management found that competence varied significantly between studies and further research is necessary to identify the most effective training strategies; however, clinician instruction on AAI administration correlates significantly with parental comfort with AAI use 15,16 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, OVA is one of the egg allergens, and separating and purifying OVA is crucial for exploring the mechanism and improving egg allergenicity [ 51 , 52 ]. High-purity OVA is often used to investigate the structure and properties of proteins and as an experimental model for allergy [ 53 , 54 , 55 ]. In addition to its functional and nutritional properties, OVA has also been found to have potential therapeutic applications.…”
Section: Fractionation Of Egg Proteinsmentioning
confidence: 99%